PERUBAHAN JERAPAN P PADA ULTISOL AKIBAT PEMBERIAN CAMPURAN ABU TERBANG BATUBARA-KOTORAN AYAM - Agus Hermawan; Sabaruddin Sabaruddin; Marsi Marsi; Renih Hayati; Warsito Warsito (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
TITLE : CHANGES OF P SORPTION ON ULTISOL DUE TO ADDITION OF COAL FLY ASH-CHICKEN MANURE MIXTURE. High soil P sorption which result in low P availability for plants is one of important constraints in Ultisols. The objective of current research was to study the effect of coal fly ash-chicken manure mixture (FA-CM) on the changes in P sorption and availability in Ultisols. Two treatments - FA-CM mixture (w/w of 1:1) at the rate of 0, 15, 30, 45 and 60 ton ha-1, and P fertilization at the rate of 0, 87, 174, 261 and 348 kg P2O5 ha-1 - were tested. These treatments were arranged according to Factorial Completely Random Design with three replicates. Results of current research showed that FA-CM and P rates and their interaction significantly affected the values of point of zero charge (PZC), pH and soil negative charges. FA-CM mixture as a soil ameliorant decreased P sorption but it increased available P in Ultisols by increasing both soil pH and negative charges. The application of FA-CM at 30 tons ha-1 and P at 174 kg P2O5 ha-1 resulted in better increases in soil charges than any other combinations. However, the lowest P sorption (127.07 mg kg-1) and the highest available P (102.21 mg kg-1) was resulted in by the applications of 42.64 tons of FA-CM ha-1 and 261 kg P2O5 ha-1.